School nutrition programs in Dubai: a landscape analysis - Reem AlGurg; Reem AlGurg; Nour Abu Mahfouz; Farah Otaki; Farah Otaki; Agnes Paulus; Agnes Paulus; Amar Hassan Khamis; Mohamad Alameddine (Frontiers in Public Health)
BackgroundLittle is known about the execution of School Nutrition Programs (SNPs) within schools across the public and private sectors in Dubai, United Arab Emirates. This highlights the importance of capturing an inside perspective about the specificities of the SNPs in order to ensure their effective, efficient, and equitable implementation across schools, irrespective of whether they are public or private.ObjectiveThe overall purpose of this study was to develop insight into SNPs in Dubai, and to investigate the difference in characteristics of those SNPs, between the public and private sectors.MethodsThis study relied on a quantitative tailor-made survey. The data were analyzed using SPSS; descriptive analysis consisted of computing the proportions for all the variables. In terms of inferential analysis, chi-square test of independence was selected to determine whether there are associations between the categorical variables (i.e., the various characteristics of the SNPs, and whether the corresponding schools are public or private).ResultsOut of 75 school representatives who were invited to participate in the current study, 60 responded, of whom 48 school representatives indicated that their respective schools had SNPs. These 48 SNPs had varying implementation scopes and program compositions (i.e., combination of initiatives) of Parents’ Involvement, Lunch Box, Educational Curriculum, Hydration, Awareness Activities, School Canteen, and/ or Food Safety and Hygiene. The stakeholders involved in developing and maintaining the respective SNPs and the intended outcomes of those programs also differed across the schools.ConclusionThis study highlights, in alignment with Sustainable Development Goals 3, 4, 9 and 17, the importance of the proposed reformation around SNPs in Dubai to take into account the governance structure on the local and national levels, quality assurance measures, stakeholder engagement, and programs’ intended outcomes and compositions. It proposes the enactment and maintenance of holistic, school-level healthy living programs that include nutrition as part of a more comprehensive approach to fostering the students’ individual and collective wellbeing.